THE DYNAMICS OF GOVERNMENT POLITICAL POLICY TO AGAMA DJAWA SUNDA (ADS); Study of Historical Analysis and Its Development - Anwar Sanusi; Azmi Rizaldy (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2021)
Sadewa Alibassa Koesoema Widjajaningrat or known as Madrais was born in Kuningan and had studied religious insight at several Islamic boarding schools. However, the pattern of his life was dominated by mysticism, so that he feels he has received revelation from God. It was on the basis of receiving this revelation that Madrais founded the Agama Djawa Sunda (ADS). The Agama Djawa Sunda (ADS) is one of the local belief systems in Indonesia and had developed in the Cigugur, Kuningan and several other areas in West Java. In its development, it often experiences obstacles and resistances. Even so, its adherents are still able to maintain the Agama Djawa Sunda (ADS) and move according to the times. The basic conception of Javanese-Sundanese belief lies on three main pillars, namely the Concept of God, Pikukuh Tilu and Customary Law (Circumcision, Marriage and Death) according to the teachings developed in ADS.